Kahoot as a Digital Game-Based Instruction for EFL Young Learners: Students' Perceptions - Melisa Khoyyiroh Harahap; Utami Dewi; Ernita Daulay (Universitas Islam Negeri Palopo, 2025)
This study explores young learners’ perceptions of Kahoot as a digital game-based instruction tool in English as a Foreign Language (EFL) classrooms. The research was conducted with 18 fourth-grade students (ages 9–10) at a private elementary school in Medan, North Sumatra, Indonesia. Most participants were at beginner to lower-intermediate English proficiency levels with varied digital literacy. Data were collected over a period of three weeks using observation and interviews and analyzed thematically. Findings revealed that Kahoot positively influenced students’ learning experiences in several ways. First, it significantly increased motivation and engagement, with 14 students reporting greater enthusiasm compared to textbook-based lessons. Second, all students highlighted the fun and interactive nature of Kahoot, supported by visual and auditory features that encouraged participation. Third, 12 students emphasized its effectiveness in vocabulary and grammar acquisition, while half (9 students) reported increased self-confidence in language use. However, challenges were also identified, including technical issues, limited variety of activities, and stress caused by competition for a few learners. Overall, the study concludes that Kahoot can serve as an effective supplement to EFL instruction for young learners, fostering motivation, confidence, and language acquisition. Practical recommendations are provided for teachers, policymakers, and developers, along with suggestions for future research.